Student Satisfaction and Perception of The Role of Guidance and Counseling Services in Junior High Schools in Cilegon City - Rani Maharani; Uman Suherman; Ibrahim Alhakim (Journal of Education and Counseling (JECO), 2025)
Student satisfaction serves as a fundamental indicator for evaluating the effectiveness of Guidance and Counseling services in educational settings. This study aims to assess student satisfaction levels and perceptions regarding the role of guidance and counseling services in Junior High Schools in Cilegon City. Utilizing a quantitative descriptive approach, data were collected from 311 students selected via random sampling from a population of 7,583. The analysis employed descriptive statistics to measure central tendencies and data distribution. The results indicate that overall student satisfaction falls within the high category (Mean = 3.40), as does the perception of the guidance and counseling service's role (Mean = 3.33). Students responded positively to interpersonal aspects, particularly counselor empathy and the assurance of confidentiality. However, the study identified significant gaps in specific areas, notably the lack of effective academic interventions for low-achieving students and dissatisfaction with the physical comfort of counseling facilities. The findings suggest that while guidance and counseling services are generally effective and well-received, strategic improvements are necessary. To optimize service quality, schools must prioritize proactive academic support, enhance physical facilities, and ensure continuous professional development for counselors. These measures are essential for transforming guidance and counseling into a holistic instrument for student development.